Return to Work and Sport Following Distal Triceps Repair. Issue 7 (31st July 2020) - Manderle, Brandon; Polce, Evan; Williams, Brady; Nicholson, Gregory; Fernandez, John; Wysocki, Robert; Forsythe, Brian; Cole, Brian; Verma, Nikhil; Beletsky, Alexander
Objectives: Outcomes following distal triceps repair are important in order to properly counsel patients on expected postoperative function. Of particular interest are metrics regarding return to work and return to sport, including when return can be expected and at what intensity level. The purpose of this study is to establish important return to sport and work expectations for patients undergoing distal biceps repair. Methods: A prospectively maintained institutional database was retrospectively reviewed for all patients who underwent distal biceps repair since 2004 with minimum 2-year follow-up. A patient survey was conducted over phone with regard to preoperative and postoperative participation in sports, level of intensity, and maximum weight repetitions of barbell and dumbbell biceps curl, bench press, and consecutive push-ups. Mayo Elbow Performance Score (MEPS) and The Disabilities of the Arm, Shoulder and Hand Score (QuickDASH) were collected preoperatively and at final follow up. T-tests and chi-squared analysis was used to examine continous and categorical outcome variables, respectively. Results: A total of 70 patients (41 male) were contacted for final follow-up information. Average age was 48.42 + 13.32 and average time from initial injury to surgical intervention was 3.12 + 2.88 months. 81% of the injuries involve lifting of heavy objects, and 27.7% occurred during sport. Ten percent (n=7) of patients returned to the operating room, most commonly for ulnar nerve repair. Return to work was achieved in 86.3% of patients, occurring at an average of 2.87 months. Heavy duty status workers returned at significantly later time points than sedentary or light duty status workers (5.35 vs. 1.21 months, p<0.01). 81.4% of patients returned to the same or higher level of work. Return to sport was achieved by 79.7% of patients at an average of 3.32 months. 73.9% of patients were either satisfied or very satisfied with their ability to work, and 68.6% were satisfied or very satisfied with their ability to play spots. All competitive athletes (n=11) returned to either the same or higher level of intensity following surgery. Conclusion: Surgical repair of a distal triceps injury results in reliable return to work and sport, with the majority of patients returning to the same physical intensity of work and the same intensity of sporting, respectively. Competitive athletes demonstrate particularly impressive results with heightened return to sport rates at the same or greater intensity level, suggesting motivation level may have a role in determining successful return to sport. Our data may be utilized to better inform the shared decision-making process between providers and patients when considering surgical intervention for distal triceps injuries.